Albania : Enhancing Tax Administration Capacity During Challenging Times. (IMF Staff Country Reports; Country Report, 2022)
The purpose of this mission was to assist the General Directorate of Taxes (GDT) in taking stock of reform efforts and provide advice on future efforts. In recent years, the GDT made solid progress in realizing its reform agenda. The mission took stock of the reform achievements and identifies areas which require further improvement.